Organisational behaviour : an Asia-Pacific perspective - Wood, Jack Maxwell. (J. Wiley, 1998)
This book is divided into seven parts: Organisational Behaviour and the Contemporary Environment; Managing individuals in Organisations; Managing Groups in Organisations; managing Organisations; Managing the processes of Organisational Behaviour; Managing Organisational Dynamics; and Case Studies.